PASSKEYS AND THE PARADIGM SHIFT IN AUTHENTICATION: A COMPREHENSIVE ANALYSIS OF PHISHING-RESISTANT IAM - Sharath Chandra Thurupati, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article examines the emergence of passkeys as a revolutionary authentication method in the Identity and Access Management (IAM) field. As cybersecurity threats evolve, traditional password-based systems have proven increasingly vulnerable to phishing attacks, credential stuffing, and other security breaches. Passkeys, leveraging public-key cryptography and the FIDO2 standard, offer a promising solution by providing phishing-resistant, user-friendly, and device-bound authentication. This article comprehensively analyzes passkey technology, exploring its functionality, advantages over traditional methods, and potential impact on IAM practices. We evaluate the security enhancements and improved user experience passkeys offer while addressing adoption challenges and future research directions. Our findings suggest that passkeys represent a significant paradigm shift in authentication, with far-reaching implications for cybersecurity across various industries and the potential to reshape the landscape of digital identity protection fundamentally.